Key performance indicators in elite female football: Associations between sprints, duels, and match results - Villaseca-Vicuña, R.; Barrera-Díaz, J.; Otero-Saborido, F.; Zabaloy, S.; Palorames, E.; Sarmento, H. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study aimed to compare and analyze the physical, technical, and tactical performance of players according to match results and to examine the associations between these indicators and match outcomes in official FIFA competitions.